In situ preparation of molybdenum-dioxide-incorporated carbonized silk fiber and its application in supercapacitors - Ji, Yansong; Zhang, Xiaoning; Zhu, Yong; Norton, Michael L.; Shen, Lunfu; Tan, Wenhui; Zheng, Xi; Li, Shuo (Frontiers in Bioengineering and Biotechnology, 2022)
A previous study found that the capacitive behavior of nanoparticles fed to the silkworm can be delivered to carbonized silk fibers, which can be used to fabricate electrodes for the construction of flexible supercapacitors. However, the tendency of nanoparticles to aggregate decreases the quantity of nanoparticles that enter the silk and therefore reduces the capacitance performance of the prepared carbonized silk. Here, we sprayed ammonium molybdate tetrahydrate (AMT) on the surface of mulberry leaves used for feeding silkworms and investigated the effect of feeding AMT on the growth of silkworms and the properties of spun silk. The precursor incorporated into the silk was converted into scattered MoO2 NPs, which were embedded within the carbonized silk fiber (CSF) via carbothermal reduction. The specific capacitance of CSF obtained from silkworms fed with an aqueous solution of AMT-treated mulberry leaves reached up to 298 F/g at 0.2 g/A, which is much higher than that of the control group (102 F/g). Since AMT is highly water-soluble, and its concentration can be easily modulated, we believe that the proposed strategy is feasible for the large-scale fabrication of CSF with enhanced capacitive performance.